The performance of size grading machine of robusta green coffee bean using oscillating sieve with swing along width direction - N Srisang; W Chanpaka; T Chungcharoen (My University, 2019)
Abstract Size grading is one of important processes for producing the Robusta green coffee bean because it can increase the value of green coffee bean and decrease the problem in the manufacturing process, especially roasting process. Therefore, the objective of this work was to investigate the effects of inclined angle and oscillating revolution speed on the performance of size grading machine of Robusta green coffee bean using oscillating sieve with swing along width direction. When increasing the inclined angle from 4 to 6 degree, the weight purity index and the clogging sieve percentage were decreased. For the size grading efficiency, it found that the size grading efficiency was increased when the inclined angle increased from 4 to 5 degree. However, the size grading efficiency was decreased when increasing the inclined angle from 5 to 6 degree. When considering in term of oscillating revolution speed, the increase of oscillating revolution speed provided the decrease of weight purity index, size grading efficiency and clogging sieve percentage. The appropriate condition for using the size grading machine of Robusta green coffee bean using oscillating sieve with swing along width direction is the inclined angle of 5 degree and the oscillating revolution speed of 185 rpm.
Keywords: Sieve (category theory); Grading (engineering); Sieve analysis; Coffee research and impacts